Association of perioperative P2Y12 inhibitor administration with outcomes for tandem occlusion: RESCUE AT-LVO sub-study - Yoshimoto, Takeshi; Yamagami, Hiroshi; Sakai, Nobuyuki; Uchida, Kazutaka; Shirakawa, Manabu; Beppu, Mikiya; Toyoda, Kazunori; Matsumaru, Yuji; Matsumoto, Yasushi; Todo, Kenichi; Hayakawa, Mikito; Shindo, Seigo; et al. (Frontiers in Neurology, 2024)
BackgroundWe aimed to clarify the association between intraoperative P2Y12 inhibitor administration during EVT and clinical outcomes in patients with anterior circulation TO stroke.MethodsAmong consecutive patients with acute ischemic stroke (AIS) enrolled in the Recovery by Endovascular Salvage for Cerebral Ultra-acute Embolic and Atherothrombotic Stroke with Large Vessel Occlusion Registry from 2016 to 2019, those with anterior circulation TOs who underwent EVT were analyzed. These patients were categorized into the following groups: those who received P2Y12 inhibitors during the perioperative period and those who did not receive P2Y12 inhibitors. The outcomes included good functional outcomes, as indicated by a modified Rankin Scale score of 0–2 at 90 days, and the incidence of symptomatic intracranial hemorrhage (SICH) was compared between the two groups. Multivariate logistic regression models were used to assess the association of outcomes with perioperative P2Y12 inhibitor administration. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using the group that did not receive P2Y12 inhibitors as the reference. The perioperative period included the period in which antithrombotic therapy was administered immediately before EVT and during the operative period.ResultsWe enrolled 242 patients with AIS with anterior circulation TOs (42 females [17.4%]; median age, 76 [interquartile range, 69–81] years). Patients who received P2Y12 inhibitors during the perioperative period (n = 131) showed a higher frequency of carotid artery stenting than those who did not receive perioperative P2Y12 inhibitors (n = 111; 86.3% vs. 42.3%, p < 0.01). Furthermore, patients who received perioperative P2Y12 inhibitors during the perioperative period had a higher incidence of good functional outcomes than those who did not receive perioperative P2Y12 inhibitors (42.0% vs. 32.4%; adjusted OR: 6.65, 95% CI: 1.88–23.53), with no significant differences between the groups in the incidence of SICH (5.3% vs. 8.1%; OR: 0.44; 95% CI: 0.09–2.09).ConclusionPerioperative administration of P2Y12 inhibitors may be associated with a higher frequency of good functional outcomes in patients undergoing EVT for AIS with anterior circulation TOs. However, since several confounding factors are involved in this sub-analysis of EVT for anterior circulation TOs, further studies are warranted.